FAT FLUX: enzymes, regulators, and pathophysiology of intracellular lipolysis - Rudolf Zechner (EMBO Molecular Medicine)
Abstract The great 19th century French physiologist Claude Bernard reasoned “Man can learn nothing except by going from the known to the unknown”. This premise is particularly applicable to the progression of discoveries made in the field of fat metabolism since Bernard's time. Beginning with his groundbreaking discovery of fat digestion (later termed “lipolysis”) in 1848, research addressing the basic processes of cellular storage and mobilization of fat has steadily advanced. Even after 150 years of research dedicated to lipolysis, exciting new principles have continued to emerge in the last 10 years. This Perspective summarizes these recent landmark discoveries in the field and emphasizes their relevance for the pathogenesis of extremely prevalent diseases such as obesity, heart disease, and cancer.